Hemodynamic impacts of left coronary stenosis: A patient-specific analysis - Chaichana, Thanapong; Sun, Zhonghua; Jewkes, James (Wroclaw University of Technology, 2013)
This study analyses the hemodynamic variations surrounding stenoses located at the left coronary bifurcation, and their influence on the wall shear stress (WSS) in realistic coronary geometries. Four patients with suspected coronary artery disease were chosen, and coronary models were reconstructed based on high-resolution CT data. The coronary stenoses were observed at the left circumflex and left anterior descending branches, resulting in a lumen narrowing of >50%. Flow analysis was performed using computational fluid dynamics, to simulate the cardiac flow conditions of the realistic individual patient geometry. Blood flow and WSS changes in the left coronary artery were calculated throughout the entire cardiac phases. Our results revealed that the recirculation regions were found at the post-stenotic locations. WSS was found to increase at the stenotic positions in all four patients. There is a strong correlation between coronary stenosis and the hemodynamic changes, which are reflected in blood flow pattern and WSS, based on the realistic left coronary geometries.